(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2025)
This case study investigates the often-overlooked cultural and natural treasures of Sudan, framed through the lived experiences of an expatriate family from 2020 to 2023. It explores renowned sites such as the ancient Nubian pyramids, the burgeoning tourism prospects along the Red Sea near Port Sudan, and the symbolic meeting point of the Blue and White Niles in Khartoum. Highlighting Sudan’s significant, yet underdeveloped, potential for archaeological, cultural, and eco-tourism, the research also delves into systemic obstacles hindering tourism growth, including inadequate infrastructure, bureaucratic hurdles, and a lack of global visibility. The abrupt onset of civil conflict in 2023 not only disrupted nascent tourism initiatives but also jeopardised invaluable cultural assets. Through the amalgamation of personal narrative with insights from academic literature, this study emphasises the urgent need for international engagement to both safeguard Sudan’s rich heritage and reimagine its tourism prospects in a post-conflict landscape.